MEMAHAMI POLA PEMBAHARUAN PAHAM KEPEMIMPINAN MANAJEMEN PERWAKAFAN DI INDONESIA (ZISWAF: Jurnal Zakat dan Wakaf, 2016)
The tradition of the Indonesian Islamic community who tend to interpret the waqf as ibadahtabarru 'which has dimensions that are sunnah Award, in the realm of implementation are still heavily influenced understand professed by the majority of society itself, the local customs. In addition, it is also influenced by religious ideology, which is a habit to take legal actions, especially on the ground perwakafan orally on the basis of mutual trust to a particular person or institution, and this practice many people do before the Law No. 5 of 1960 on Basic Regulation of Agrarian and Government Regulation No. 28 Year 1977 on Land Owned perwakafan. The phenomenon of this tradition implications perwakafan in Indonesia has not experienced encouraging development for the benefit of the people, even suppose many emerging new issues such as loss of property for religious use, utilization is not appropriate designation endowments, low ability to manage so many waqf property displaced and so forth.Pattern management leadership implementation waqf ago is still considered consumer-static, meaning that the management of property endowments are less able to provide benefits to the community, it can be seen from the model of leadership within the agency kenazhiran paternalistic and absence of adequate control, the recruitment of human resources more focused on ketokoan clerics, scholars, religious teacher regardless of professionalism, no clear operational standards empowerment and so forth. in line with the enactment of Law No. 41 2004 quiet Endowment and Government Regulation No. 28 Year 1977 on Land Owned perwakafan, then it started last major improvement in the management of the renewal perwakafan Indonesia understands both institutionally related empowerment, development and coaching, management kenazhiran and others.